X-ray radiation shielding of CeO2 doped borosilicate glasses and their luminescence characteristics. (February 2022) - Kaewjaeng, S.; Boonpa, W.; Kothan, S.; Kim, H.J.; Jumpee, C.; Rajaramakrishna, R.; Tungjai, M.; Kaewkhao, J.
Abstract: The novel shielding materials from (55-x) SiO2 : 13B2 O3 : 1Al2 O3 : 4.5BaO: 6.3CaO: 0.2Sb2 O3 : 20Na2 O: xCeO2 where x = 1, 2, 3, 4 and 5 mol% glasses have been fabricated at different CeO2 concentration by melt-quenching technique and studied the luminescence and radiation shielding properties. The transmission spectra show red-shift in UV range, due to higher Ce concentration in the glass matrix. The emission bands of glasses around 393 nm were observed from the 5d-4f transition of an electron in the Ce 3+ ion. In the present glass matrix doped with CeO2 shows oxidation state of both Ce 3+ and Ce 4+ . Decay curves are also investigated and found to be less than 100 ns. The X-rays shielding properties such as half-value layer (HVL), tenth value layer (TVL), mean free path (MFP), and linear attenuation coefficients (μ) of glass were investigated. The HVL values of glass samples at 5 mol% has better shielding behavior than commercial x-ray windows. The obtained results from the measurements suggests that these glasses are potential host for radiation shielding material application and also UV emitting device applications. Highlights: Novel Borosilicate Shielding glasses was fabricated. Emission bands around 393 nm were observed from 5d-4f transition by the Ce3+ ions. Less than 100 ns was observed for the lifetime of these ions in the borosilicate glasses. HVL values of glass samples at 5 mol% of CeO2 content show better results than commercial x-ray windows. The ratio of Ce 3+ and Ce 4+ were evaluated for 1, 3 and 5 mol% CeO2 content using XANES.